Development and Evaluation of a Prediabetes Decision Aid in Primary Care: Examining Patient-Reported Outcomes by Language Preference and Educational Attainment. Issue 3 (June 2021) - Bandi, Keerthi; Vargas, Maria C.; Lopez, Azucena; Cameron, Kenzie A.; Ackermann, Ronald T.; Mohr, Loretta; Williams, Geoffrey C.; Fagerlin, Angela; Kirley, Kate; Hodge, Heather; Kandula, Namratha R.; O'Brien, Matthew J.
Purpose: The purpose of this study was to examine the development and preliminary effectiveness of a novel Prediabetes Decision Aid on adoption of intensive lifestyle interventions (ILIs) and metformin. Little research has focused on increasing uptake of these evidence-based treatments, especially among non-English speakers and those with low educational attainment. Methods: Investigators developed an English and Spanish decision aid displaying information about type 2 diabetes (T2DM) risk and treatments to prevent T2DM and prompting patients to identify next steps for management. This pilot study was a single-arm, pretest-posttest trial of 40 adult patients with prediabetes, obesity, and ≥1 office visit within the prior 12 months. Participants reviewed this tool briefly with a study team member, and data were collected on 3 coprimary outcomes: knowledge about T2DM risk, decisional conflict, and intention to adopt treatment. Exploratory outcomes included subsequent documentation of prediabetes in chart notes and adoption of ILIs or metformin. Results: Almost all participants were women, with nearly half expressing Spanish language preference and low educational attainment. A nonsignificant increase in knowledge was observed across all subgroups. Decisional conflict was significantly reduced from pretest to posttest and was similar between subgroups defined by language preference and educational attainment. While intention to adopt ILIs increased across all subgroups, this change was only significant among Spanish speakers and participants with low educational attainment. At 6 months, 17 participants had subsequent provider documentation of prediabetes, and 12 adopted ILIs or metformin. Conclusions: The decision aid improved patient-reported outcomes and promoted treatment adoption in a diverse patient sample.